Михайло Степанович Регеда. Приречений бути успішним, (до 50-річчя від дня народження) - Федорів, Я.-Р.М. (Медична гідрологія та реабілітація, 2010)
Doctor of Medical Sciences, professor M. S. Reheda, rector Magnificus of Medical Institute in Lviv, head of the Department of pathophysiology of Danylo Halytskyi State Medical University in Lviv. Prepared 5 candidate of medical sciences. Autor of 540 scientific articles, include 63 books.